2021
DOI: 10.1089/jwh.2020.8948
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Coronavirus Disease 2019 (COVID-19) Hospitalization and Mortality

Abstract: Background: To investigate sex differences in coronavirus disease 2019 outcomes in a large Illinois-based cohort. Methods: A multicenter retrospective cohort study compared males versus females with COVID-19 infections from March 1, 2020, to June 21, 2020, in the Rush University System. We analyzed sex differences in rates of hospitalization, intensive care unit (ICU) admission, vasopressor use, endotracheal intubation, and death in this cohort. A multivariable model correcting for age and sum of comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 29 publications
7
59
2
1
Order By: Relevance
“…Similar patterns were noted in the study of COVID-19 mortality in Massachusetts (17). Our findings reflect a growing body of literature documenting a disproportionate burden of severe and fatal COVID-19 cases among men and racial/ethnic minorities (19)(20)(21)(22)(23)(24)(25). It is important to note that the occupational disparities in COVID-19 fatalities that we found could not be attributed solely to differences in employment by sex or race/ethnicity.…”
Section: Discussionsupporting
confidence: 83%
“…Similar patterns were noted in the study of COVID-19 mortality in Massachusetts (17). Our findings reflect a growing body of literature documenting a disproportionate burden of severe and fatal COVID-19 cases among men and racial/ethnic minorities (19)(20)(21)(22)(23)(24)(25). It is important to note that the occupational disparities in COVID-19 fatalities that we found could not be attributed solely to differences in employment by sex or race/ethnicity.…”
Section: Discussionsupporting
confidence: 83%
“…We focus the attention of this paper on quantifying disparities in population-level COVID-19 mortality. Substantial scientific research has uncovered disparities in COVID-19 mortality outcomes in the U.S. by race/ethnicity (e.g., (3, 4, 5, 6, 7, 8, 9, 10, 11)), as well as between males and females (e.g., (12, 13, 14, 15, 16, 17, 18, 19)). However, research on U.S. population-level disparities in COVID-19 mortality outcomes across the intersection of race/ethnicity and sex has been limited, largely due to the absence of requisite publicly available data, which represents a critical research gap in the quantification and understanding of the nature of population-level disparities in COVID-19 mortality outcomes between subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Hospital mortality is estimated to be less than 5% for individuals younger than 40 years, 35% for patients aged 70 to79 years, and more than 60% for people 80 to 89 years of age [ 4 ]. Concerning sex, a similar mortality pattern was reported in Europe, while a study carried out in the US showed that male sex was independently associated with death, hospitalization, and intensive care unit admissions [ 5 , 6 ]. Individuals undergoing kidney transplants or dialysis; and patients with cancer, diabetes, and neurologic or cardiovascular diseases are suggested to be at increased risk for mortality [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 54%